Development of Virgin Coconut Oil Fermented Tank Using Teak Wood Powder Insulator - Rudi Kurniawan Arief; Muhamad Ramadhan Kasman; Armila Armila; Irfan Hilmy (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2022)
One of the processed products derived from coconut that has great demand in the world of health and beauty industry is virgin coconut oil or known as VCO. Most VCO is processed manually using conventional methods with unhygienic plastic containers and placement in open spaces by the home industries. This research is to develop a VCO-fermented tank that was able to maintain hygiene and low temperature during the fermentation process by using SS403 and teak wood insulation as the main materials. This research carries on by comparing the fermentation process and results between the conventional method and the new VCO tank. 41% VCO is produced from raw coconut milk using a new VCO tank which is 5% higher than the conventional method. The VCO fermented tank produced more VCO and was able to maintain lower temperatures compared to the conventional method and also can be operated with less procedure order.     Keywords: Fermentation Tank, Temperature Retaine, VCO, Virgin Coconut Oil